Adulteration of Honey on the Cape Coast Market in the Central Region of Ghana - Benjamin, Bartels; Ernestina, Aggrey; Yao, Gadzekpo Victor Patrick (International Journal of Environment, Agriculture and Biotechnology, 2023)
Background and objectives: This research is driven by the need to combat the growing concern of honey adulteration, a practice that compromises the quality and authenticity of this natural product. Adulteration of honey is a pressing concern that compromises its quality, authenticity, and nutritional value. This study investigates the presence of adulterants in honey samples collected from the Cape Coast metropolis in the Central Region of Ghana. Methods: Seven honey samples were analyzed. They were selected from different outlets in the metropolis. Laser- induced fluorescence (LIF) technique was employed to identify potential adulterants by examining the fluorescence spectra of the samples. The fluorescence patterns were compared to a reference database to determine the authenticity of the honey. Results: The LIF analysis revealed distinct fluorescence patterns among the samples, indicating potential adulteration. The control sample exhibited a characteristic fluorescence profile consistent with pure honey, while certain samples exhibited altered fluorescence spectra. This deviation in fluorescence patterns strongly suggests the use of additives or adulterants in the honey samples. Conclusion: The findings indicate the presence of adulteration in the samples. The altered fluorescence spectra observed in some samples strongly suggest the use of adulterants, potentially compromising the quality and authenticity of the honey. To combat honey adulteration effectively, stringent regulatory measures, increased consumer awareness, and continuous monitoring are necessary.